Facile Synthesis of Mesoporous NiCo2O4 Nanosheets on Carbon Fibers Cloth as Advanced Electrodes for Asymmetric Supercapacitors - Xiang Zhang (Nanomaterials)
The NiCo2O4 Nanosheets@Carbon fibers composites have been successfully synthesized by a facile co-electrodeposition process. The mesoporous NiCo2O4 nanosheets aligned vertically on the surface of carbon fibers and crosslinked with each other, producing loosely porous nanostructures. These hybrid composite electrodes exhibit high specific capacitance in a three-electrode cell. The asymmetric supercapacitor (NiCo2O4 Nanosheets@Carbon fibers//Graphene oxide) displayed a high specific capacitance of 91 F g−1 and excellent cycling stability with a capacitance retention of 94.5% at 5 A g−1 after 10,000 cycles. The device also achieved a notable energy density of 52 Wh kg−1 coupled with a power density of 3.5 kW kg−1 and a high power density of 7.1 kW kg−1 with an energy density of 21 Wh kg−1. This study shed light on the great potential of this asymmetric device as future supercapacitor.